High Interleukin-8 Levels Associated With Decreased Survival in Patients With Cirrhosis Following Transjugular Intrahepatic Portosystemic Shunt - Liu, Guofeng; Wang, Xiaoze; Yang, Tingting; Yan, Yuling; Xiang, Tong; Yang, Li; Luo, Xuefeng (Frontiers in Medicine, 2022)
Background Serum cytokines—reflecting systemic inflammation has been associated with the risk of decompensation and mortality in patients with cirrhosis. However, the role of systemic inflammation in patients with cirrhosis undergoing transjugular intrahepatic portosystemic shunt procedure remains unknown. Patients and Methods Patients with cirrhosis who received transjugular intrahepatic portosystemic shunt between June 2015 and September 2017 were included. Portal and hepatic venous blood samples were obtained intraoperatively; serum cytokine levels (IL-10, IL-17A, IL-1RA, IL-8, and CXCL10) were measured in 105 patients. Associations with survival and other outcomes during long-term follow-up (median: 1,564 days) were assessed using logistic regression. Results IL-17A and CXCL10 levels were higher in the portal than in the hepatic veins, whereas IL-1RA levels were higher in the hepatic than in the portal veins. However, IL-8 or IL-10 levels between hepatic and portal veins showed no differences. Multivariate analysis demonstrated that Child–Pugh scores (P = 0.017, HR: 1.484, 95% CI: 1.072–2.055) and IL-8 level in hepatic veins (P < 0.001, HR: 1.043, 95% CI: 1.019–1.068) were independent predictors for mortality during long-term follow-up, with an optimal cut-off of 5.87 pg/ml for IL-8 in hepatic veins. Patients with hepatic IL-8 levels < 5.87 pg/ml had significantly higher cumulative survival rates (98.4 vs. 72.9% at 1 year, 98.4 vs. 65.3% at 2 years, 96.7 vs. 60.3% at 3 years, 94.2 vs. 60.3% at 4 years; P < 0.0001). Conclusions IL-8 levels in hepatic veins may reflect liver cirrhosis severity. Elevated IL-8 levels suggest shorter survival in patients receiving TIPS.